2018
DOI: 10.1007/s11069-018-3493-7
|View full text |Cite
|
Sign up to set email alerts
|

Population vulnerability to tsunami hazards informed by previous and projected disasters: a case study of American Samoa

Abstract: Population vulnerability from tsunamis is a function of the number and location of individuals in hazard zones and their ability to reach safety before wave arrival. Previous tsunami disasters can provide insight on likely evacuation behavior, but post-disaster assessments have not been used extensively in evacuation modeling. We demonstrate the utility of postdisaster assessments in pedestrian evacuation modeling for tsunami hazards and use the US territory of American Samoa as our case study. We model pedest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…At DART 51426 (southeast of the epicenter), a leading crest followed by a deep trough from the combined thrust and normal faulting was recorded. The comparison with the DART and Apia tide gauge records corroborates the work of Dilmen et al (2018) and Wood et al (2018) in which a leading trough was observed at the Pago Pago Tide Gauge in Tutuila and at DART 51425 in the north, and a leading crest at DART buoys 51426 and 54401 south of the epicenter.…”
Section: Propagationsupporting
confidence: 85%
See 4 more Smart Citations
“…At DART 51426 (southeast of the epicenter), a leading crest followed by a deep trough from the combined thrust and normal faulting was recorded. The comparison with the DART and Apia tide gauge records corroborates the work of Dilmen et al (2018) and Wood et al (2018) in which a leading trough was observed at the Pago Pago Tide Gauge in Tutuila and at DART 51425 in the north, and a leading crest at DART buoys 51426 and 54401 south of the epicenter.…”
Section: Propagationsupporting
confidence: 85%
“…(2018) and Wood et al. (2018) in which a leading trough was observed at the Pago Pago Tide Gauge in Tutuila and at DART 51425 in the north, and a leading crest at DART buoys 51426 and 54401 south of the epicenter.…”
Section: Results and Interpretationmentioning
confidence: 84%
See 3 more Smart Citations